Religious Heritage Dynamics. A systematic assessment of Alentejo region (South of Portugal) as a driver for a sustainable development - Volzone, R. (European Sustainable Religious Heritage, 2023)
Religious built heritage has for centuries played an essential role in Europe, shaping social, economic, environmental and cultural values. Places of worship have constrained territorial development and are still references in current urban and rural areas. In Portugal – as in the rest of Europe – social issues (less worshipers, priests, pastors and fewer consecrated vocations), but also environmental and economic ones (reduction of parishes and territorial changes) lead to the abandonment, low utilization rate or redundancy of religious buildings. This study aims a better understanding of the Portuguese religious heritage dynamics, which can contribute to the sustainable development of rural and low-density territories. Starting from Alentejo region (southern-hinterland Portugal), with focus on monasteries and convents, an unprecedented systematic assessment is developed. This is based on a literature review, census and mapping, on-site surveys, characterization of owners, new uses and conservation state, interviews with local administrations and building owners. Collected data were, then, cross-referenced with regional and municipal policies on culture and heritage. Finally, it is proposed to look at the few cases linked to the cultural and creative tourism, investigating this alternative as an engine for more sustainable development in rural and low-density regions.